PENERAPAN STRATEGI PEMBELAJARAN AKTIF BINGO REVIEW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMAN 4 PEKANBARU - Desi Mareti Nandari; R. Usman Rery; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to increase student learning achievement on the topic of structure atoms and the periodic system of elements in class XI IPA Senior High School (SMAN) 4 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The sample was determined after doing normality and homogeneity test of 5 classes as population and then class XI IPA 5 as experiment class and XI IPA 3 as control class. Experimental class is a class that is applied to Bingo Review strategy while the control class was not applied to Bingo Review strategy. Data analysis technique used is the t-test and N-gain normalized test. Based on data analysis of data obtained tcount> ttable is 5.22>1.67, means that the application of Bingo Review strategy can improve student learning achievement on the topic of structure atoms and the periodic system of elements in class XI IPA Senior High School (SMAN) 4 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,85. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,69.Keywords: Active Learning Bingo review Strategy, Learning Achievement, Struture of Atoms and the Periodic system of Elements